The In-Justice of a lacking fiscal control system. Case: Supreme Court of Justice of Venezuela´s Digital Platform - Vivas Roso, Jessica (Universidad Nacional del Litoral, 2021)
This article examines the impact of the inadequate exercise of fiscal control on the enjoyment of citizens' rights through the study of a specific case: the lack of functioning of the Supreme Court of Justice of Venezuela´s digital platform. During 2018 and 2019, the highest court of the Republic allocated significant sums of public economic resources to the execution of a project called “Modernization of the technological platform of the Supreme Court of Justice”, however, said website throughout the year 2020 has not been working properly. This situation, on the occasion of the COVID-19 pandemic and the measures of social distancing and mandatory quarantine imposed by the Venezuelan State, has generated the violation of the rights of access to justice and effective judicial protection of citizens, who cannot rely on technological mechanisms to monitor judicial matters during the period of confinement. For this reason, the role of the Venezuelan fiscal control bodies as guarantors of the proper use of public resources and the impact this has on the enjoyment of citizens' rights, can generate an inappropriate exercise of fiscal control activity is analyzed.